Mukolitiki, ekspektoransi in antitusiki - Lipnik-Štangelj, Metoda (Medicinski razgledi, 2012)
Cough is an important disease symptom. Common causes of cough are respiratory tract infections, chronic obsuuctive pulmonary disease, asthma, lung cancer, bronchiectasie, and many other Jung diseases, but also smoking, ain'ITay foreign body. Common extra pulmonary causes of cough are gastroesophageal reflux, rhinitis with postnasal drip, etc. Cough treatment should be always directed at the underlying ca use of cough. In rare cases, it is reasonable totrem symptomaric cough, i.e. to facilitate expectoration in patients with cystic fibrosis using dornase a. Due to cough caused by upper respiratory tract infection, patients of ten opt for self~medication. The efficacy and safety of many products that are used for this purpose has not been confirmed by appropriate studies and their use may, in cenain cases, even be dangerous. In the article, mucolytic agents and expectorants that alter physical and/or chemical properties of the mucus and facilitate coughing are described. In addition, antitussive drugs which inhibit a cough reflex are also presented. They are useful when organic cause of cough could not identified, and for treatment of cough in palliative purposes. Mechanisms of action and therapeutic usefulness of drugs are described, and the most commonly used drugreprsentatives are outlined.
Keywords: Kašelj; Lung Diseases; Ekspektoransi; Cough; Pljuča, bolezni; Drug Therapy; Antitusiki; Expectorants; Acetilcistein; Antitussive Agents; Deoksiribonukleaza I; Acetylcysteine; Deoxyribonuclease I; Rastlinski izvlečki; Bromheksin; Bromhexine; Plant Extracts; Kodein; Codeine; therapy; zdravljenje; zdravila; drug